Being and Nothingness : An Essay on Phenomenological Ontology - Sartre, Jean-Paul; Translated and with an Introduction by Barnes, Hazel E. (New York Washington Square Press, 1966)
Often criticized, and all too rarely understood, the philosophy of Jean-Paul Sartre encompasses the dilemmas and aspirations of the individual in contemporary society. The principal text of the modern existentialist movement, Being and Nothingness contains the basic tenets of his thought. A work of inherent power and epic score, it provides a vivid analysis for all who would understand one of the most influential philosophic movements of our time.
Include Index.
Keywords: Existentialism -- Existential psychology -- Philosophy, French